Solubility study of tobramycin in room temperature ionic liquids: an experimental and computational based study. Issue 109 (10th November 2016) - Cunningham, Richard; Forero-Martinez, Nancy C.; Hardacre, Christopher; Youngs, Tristan G. A.; Migaud, Marie E.
Abstract : Herein, we present a computational and experimental study assessing the solubility of tobramycin1 in a series of hydrophilic room temperature ionic liquids (RTIL). Abstract : Herein, we present a computational and experimental study assessing the solubility of tobramycin1 in a series of hydrophilic room temperature ionic liquids (RTIL). We show that hydrophilic ionic liquids, in particular those containing acetate, [OAc] −, enable significantly enhanced solubilisation of tobramycin in comparison to conventional molecular solvents.